2006
DOI: 10.1002/masy.200651209
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐Nanocomposites: Towards High Performance Composite Materials

Abstract: Strong cellulose fibres, e.g. flax and hemp, are increasingly used for composites. Despite substantial advantages, the tensile strength of these fibres is limited due to their complex structure and the unavoidable imperfections of the cell wall, inherent from growth or induced by processing. Essential improvements are possible by using highly crystalline cellulose fibrils (''whiskers'') which can be isolated from the cell wall, thus eliminating the influence of adhesion and defects. Instead of complete fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Kohler (Kohler and Nebel, 2006), through comparisons of SEM pictures, specific surface, and Mercury Injection Apparatus before and after steam explosion, drew the conclusion that compared with straw without steam explosion, the porosity and permeability was improved, the pore area increased, and the total pore volume of the straw decreased through steam explosion. Cellulose is the skeleton of cell walls, and hemicellulose and lignin are the filler, with lignin and hemicellulose apparently degraded after steam explosion.…”
Section: Principles Of Steam Explosion Technologymentioning
confidence: 99%
“…Kohler (Kohler and Nebel, 2006), through comparisons of SEM pictures, specific surface, and Mercury Injection Apparatus before and after steam explosion, drew the conclusion that compared with straw without steam explosion, the porosity and permeability was improved, the pore area increased, and the total pore volume of the straw decreased through steam explosion. Cellulose is the skeleton of cell walls, and hemicellulose and lignin are the filler, with lignin and hemicellulose apparently degraded after steam explosion.…”
Section: Principles Of Steam Explosion Technologymentioning
confidence: 99%
“…12.2 and 12. 3) It has been shown that the maximum actuator performance of cellulose is at high humidity condition and decreases over time and at dry condition. In order to enhance the performance of the EAPap actuator in ambient humidity, it has been mixed or blended with carbon nanotubes, 38 chitosan, 39 IL, 40 or has been coated with PPy and PANI conductive polymer.…”
Section: Cellulose In Actuator/strain Sensormentioning
confidence: 99%
“…In order to tackle the issue of interfacial bonding, the most common approach involves modifying the chemistry of the fiber or matrix in order to improve the chemical compatibility between components. Interfacial bonding can also be increased by using nanosized forms of cellulose such as bacterial cellulose [48][49][50], microfibrillated cellulose [51][52][53], and cellulose whiskers [54][55][56][57][58] that provide an increased surface area per volume. Interfacial bonding can also be increased by using nanosized forms of cellulose such as bacterial cellulose [48][49][50], microfibrillated cellulose [51][52][53], and cellulose whiskers [54][55][56][57][58] that provide an increased surface area per volume.…”
Section: The Biocomposite Renaissancementioning
confidence: 99%